Daptomycin Resistance in Clinical MRSA Strains Is Associated with a High Biological Fitness Cost - Roch, Melanie; Gagetti, Paula; Davis, James; Ceriana, Paola; Errecalde, Laura; Corso, Alejandra; Rosato, Adriana E. (Frontiers in Microbiology, 2017)
Daptomycin remains as one of the main treatment options for Methicillin Resistant Staphylococcus aureus (MRSA). Sporadic resistance cases reported in patients treated with either daptomycin or glycopeptides are a growing concern. In a previous study, we described a clinical case of a patient with a community-acquired MRSA infection resistant to daptomycin and with intermediate resistance to vancomycin who developed a recurrent infection with a susceptible isogenic strain. In the present work, we further investigated the sequential events to determine whether the switch from a daptomycin resistance to a susceptible phenotype was due to a phenomenon of resistance reversion or recurrent infection with a susceptible strain. Pairwise competition experiments showed that the susceptible clinical recurrent SA6850 strain had increased fitness when compared to the resistant counterpart SA6820 strain. In fact, although we have demonstrated that reversion of daptomycin resistance to daptomycin susceptible can occur in-vitro after serial passages in drug free media, phylogenetic analysis suggested that the in vivo process was the result of a recurrent infection with a previous susceptible isolate carried by the patient rather than a resistance reversion of the strain. Whole genome sequence of evolved strains showed that DAP resistance in MRSA is associated with a high fitness cost mediated by mutations in mprF gene, revealed as a key element of the biological cost. Moreover, we determined that daptomycin resistance-associated fitness cost was independent of vancomycin intermediate resistance phenotype, as demonstrated in additional clinical MRSA vancomycin susceptible strains. This study highlights important observations as, despite Daptomycin offers a useful treatment option for the patients with persistent infections, it has to be carefully monitored. The high fitness cost associated to daptomycin resistance may explain the reduced dissemination of DAP resistance and the absence of DAP reported outbreaks.